Effect of the Fibers Amount and Their Length on the Thickness and Strength of Green Composites Sugarcane-Polypropylene - Sanjaya Sewucipto; Juliana Anggono; Suwandi Sugondo (Mechanova, 2015)
Sugarcane fiber has been studied as a potential reinforced fibers to develop green composites ofsugarcane fibers-polypropylene (PP). In this study, sugarcane fibers were alkali treated with 10%v/v NaOH solution for 2 hours. Sugarcane fibers added to polypropylene matrix was 3 cm, 5 cmand as their original length. They were added in the various weight percentage ratios betweensugarcane fibers to PP of 20/80, 25/75, and 30/70. Tensile test in accordance with ASTM D638-03type 1 was conducted for all specimens. The fracture surface of tensile test specimen was thenobserved by using Scanning Electron Microscope (SEM) to study the interface bonding betweensugarcane fibers and polypropylene, mixture homogeneity and breaking mechanism. Results fromthe tensile tests show that performing alkali treatment for 2 hours increases the tensile strength ofthe composites up to 20,76 MPa with the original length sugarcane fibers treated with 10% NaOHfor 2 hours in the 30/70 weight ratio percentage composite. The SEM observation shows theremoval of the lignin and hemicellulose by the NaOH solution after 2 hours of soaking whichimproves the mechanical bonding between sugarcane fiber and PP. Therefore it increased thetensile strength.